The effects of legal and extra-legal characteristics on organizational victim decision-making - Holtfreter, Kristy (Crime, law and social change, 2008)
A variety of factors influence decisions to mobilize formal social control. With few exceptions, studies considering the effects of legal (e.g., case specific) and extra legal (e.g., offender and victim characteristics) variables have concentrated on sentencing under criminal law, an outcome subject to sample selection bias given that the majority of cases never reach this stage. Analyses of earlier decision points (e.g., victim calls for service, police use of force, and arrest), have focused on street crime and single jurisdictions. A neglected research context is the organizational victim’s response to employee fraud. Using a sample of 663 fraud cases, this study applies Black’s (The behavior of law, San Diego, Academic, 1976) theory of law to victim organizations’ decisions to mobilize formal social control. Results demonstrate that extralegal characteristics weigh heavily on decisions to initiate both criminal and civil outcomes. Specifically, offenders’ education and age decreased the odds of criminal legal mobilization. Mobilization of criminal law was also more likely by government agencies. Implications for Black’s theory and directions for further research are discussed.